Surfactant charge tuning alters casein micelle structure and complexation behavior - Yang, Liying; Chen, Mengjia; Luo, Yunyan; Yang, Shuyuan; Li, Na; Sun, Yang (Food hydrocolloids, 2025)
To elucidate the mechanisms underlying the structural and complexation changes of casein micelles induced by surfactants with varying charges, the interactions of sodium dodecyl sulphate (SDS), dodecyl ammonium bromide (DTAB) and polysorbate 20 (PS-20) with goat casein micelles (GCM) have been thoroughly investigated via integrative techniques. The anionic surfactant SDS disrupted the self-assembly of caseins and induced the β-sheet into α-helix, leading to the dissociation of GCM into CCP-casein nanoclusters with a core-shell-like structure and enhancing thermal stability. DTAB, a typical cationic surfactant, triggered CCP solubilization and led the dissociation of GCM into caseins assemblies, which resulted in the transition of α-helix into β-sheet and a “necklace and bead” structure complex with decreased thermal stability. As a non-ionic surfactant, PS-20 formed an adsorbed layer on the GCM surface, stabilizing the air/water or oil/water interface with minimum alteration to the internal structure of GCM. Structural insights into GCM and surfactant-nanoclusters complexation were studied for the first time using SEC-SAXS and time-resolved SAXS. The results highlight that cooperative electrostatic and hydrophobic interactions significantly impacted the structural modulation of GCM and GCM-surfactant complexes. This study offers a molecular framework for understanding how surfactants with different charges modulate casein micelles structure, providing a guidance for designing casein-based food hydrocolloids with tailored properties. [Display omitted] •Structure of GCM and surfactant-GCM complexation were studied using SEC-SAXS and time-resolved SAXS.•SDS initiated dissociation of GCM with a core-shell structure and increased thermal stability of GCM.•DTAB triggered CCP solubilization and dissociation of GCM with a “necklace and bead” structure.•DTAB converted α-helix into β-sheet and decreased thermal stability of GCM.•PS-20 formed an adsorbed layer on GCM surface with minimum altering structure of GCM.